2010
DOI: 10.1161/circoutcomes.108.831073
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Cardiovascular Death in Racial/Ethnic Minorities Using Framingham Risk Factors

Abstract: Background-Risk factors for cardiovascular disease (CVD) derived from the Framingham study are widely used to guide preventive efforts. It remains unclear whether these risk factors predict CVD death in racial/ethnic minorities as well as they do in the predominately white Framingham cohorts. Methods and Results-Using linked data from the National Health and Nutrition Examination Survey III (1988 to 1994 and the National Death Index, we developed Cox proportional hazard models that predicted time to cardiovasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 21 publications
1
42
0
2
Order By: Relevance
“…Overall, the Framingham Risk Score calculator can determine a patient's 10-year absolute risk of CHD but may have some limitations and perhaps underestimate the risk in diverse populations [41,42,43]. The strength of associations between individual CVD risk factors differs significantly by race/ethnicity, with a greater risk for CVD mortality at younger ages in some minority individuals, suggesting that CVD risk prediction models should be validated in increasingly diverse, contemporary cohorts [43].…”
Section: Classification Of Race/ethnicity and Cmr: Limitations In Utimentioning
confidence: 99%
“…Overall, the Framingham Risk Score calculator can determine a patient's 10-year absolute risk of CHD but may have some limitations and perhaps underestimate the risk in diverse populations [41,42,43]. The strength of associations between individual CVD risk factors differs significantly by race/ethnicity, with a greater risk for CVD mortality at younger ages in some minority individuals, suggesting that CVD risk prediction models should be validated in increasingly diverse, contemporary cohorts [43].…”
Section: Classification Of Race/ethnicity and Cmr: Limitations In Utimentioning
confidence: 99%
“…We have therefore chosen to review a broad range of articles pertinent to racial and ethnic disparities in cardiovascular disease. These include papers examining racial differences in the quality of care provided for patients with myocardial infarction, 11 trends in procedure use for patients with heart failure, 12 survival after heart transplantation, 13 the relative importance of traditional and novel biomarkers of cardiovascular risk, 14 and the influence of socioeconomic factors such as living environment on outcomes. 6 We hope you find these reviews informative.…”
mentioning
confidence: 99%
“…This study identified five studies that assessed cardiovascular risk prediction models in cohorts from Latin America or Hispanic populations in the United States (5,18,21,23,24). Overall, evidence supporting the validity of CV prediction rules among these populations is scare.…”
Section: Discussionmentioning
confidence: 99%
“…Data regarding CVD burden and trends among Hispanics living in the United States is also alarming and represents the most likely cause of death among this population (5), about 31% of all deaths (6). The prevalence of heart disease is 8.1% in Hispanics and 12.1% in Caucasians (7) and the prevalence of obesity (8), diabetes mellitus, hypertension, and dyslipidemia, is generally higher among Hispanics than Caucasians (7,9).…”
mentioning
confidence: 99%